Pengaruh Pendapatan Dan Kredit Terhadap Kinerja Guru : "Studi Perilaku Guru Di Kabupaten Boyolali" - PURNOMO, EKO WULAN, Dr. Tjipto Subadi, M.Si, Dr. Suyatmini, M.Si (2017)
The aim of this research is to determine whether there is influence between income and credit to the performance of teachers in Boyolali. This research included quantitative descriptive research type with the withdrawal of the conclusion through statistical non-paramaterik analysis. The population in this research is the whole teacher in Boyolali Regency. Samples taken as many as 30 teachers at a different work unit level i.e. senior high school, junior high school, elementary school with proportional sampling techniques. With the design of ethnographic research. Required data obtained through questionnaires and documentation. Previously, questionnaire were trialed, and tested for validity and reliability. Data analysis technique used was multiple linear regression analysis, t-test, F-test, test of R2, and the relative contribution and effective. The research results obtained the regression line equation Y = 76,672 + 0,472. X1 + (-0.351).X2 The equation shows that the performance of teachers affected by the income of certified teachers and credit partially and simultaneously. Teacher perceptions about income have positive influence on performance of teachers. The results of the regression analysis gain value of tcount0.472>ttable (4.591) with p-value = 0.000 accepted on the significance level of 5%. Contribution of income towards the performance of teachers is 38.5%; Credit has negative influence on performance of teachers. The results of the regression analysis to obtain the value of tcount-0.351 > ttable (3,408) and p-value = 0.002 accepted on the significance level of 5%. Contribution of credits towards the performance of teachers is of 24.3%; Perception of teachers about income has a positive influence and credit has a negative influence on performance of teachers in Boyolali Regency. It is proven from the results of the analysis of the F test scored of larger 22.810 Fcount than Ftable of 3.35 on 5% significance level.